Circular - Jeger, George
042-0028-001 SPANISH MEDICAL AID COMMITTEE President: Rt. Hon. LORD ADDISON Vice-Presidents: Dr. CHARLES BROOK. L C.C. Dr. DAVID FORSYTH VICTOR GOLLANCZ Professor JULIAN HUXLEY Rt. Hon. Sir WILLIAM JOWITT. K.C. Sir WALTER T. LAYTON The EARL OF LISTOWEL Miss MEGAN LLOYD GEORGE, MP. TOM MANN D.N. PRITT. K.C. M.P. Miss ELEANOR RATHBONE. M.P. Miss ESTHER RICKARDS. L.C.C. JOS. ROBINSON, M.D. Dr. MAUDE ROYDEN Sir ARCHIBALD SINCLAIR. MP. BEN TILLETT Dr JANET VAUGHAN ALFRED M. WALL Miss REBECCA WEST Chairman : Dr. H.B. MORGAN. M.D. Vice-Chairman: Dr. SOMERVILLE HASTINGS, L.C.C. Treasurers: Viscountess HASTINGS W LOCKYER, J.P. Professor J.R. MARRACK, M.D., D.S.O. Hon. Secretary: Mrs. LEAH MANNING, J.P. Organising Secretary: GEORGE JEGER, J.P. Note New Address 69 GREAT RUSSELL STREET W.C.1 Telephone: HOLburn 1866 0605 March 31st 1939 EASTER Dear Friend, After consultation with the Chairman, I am directed to inform you that there will be no meeting of the Committee for the next two weeks. The next meeting will be held on Wednesday April 19th. A reminder will be sent later, with an Agenda. Yours sincerely, GEORGE JEGER (Organising Secretary) 292/946/42/28